159k views
1 vote
I need the solution

I need the solution-example-1
User Andrewmu
by
5.3k points

1 Answer

4 votes

The only thing you can do here is to try to simplify, so I'll assume that's what you want to do.


(b^2-a^2)/(2a^2+ab-3b^2)

The numerator is a difference of squares, so it's easy to factorize:


b^2-a^2=(b-a)(b+a)

In the denominator, we factorize by grouping:


2a^2+ab-3b^2=2a^2-2ab+3ab-3b^2=2a(a-b)+3b(a-b)=(2a+3b)(a-b)

So we have


(b^2-a^2)/(2a^2+ab-3b^2)=((b-a)(b+a))/((2a+3b)(a-b))=-(b+a)/(2a+3b)